PENGENALAN PELUANG DAN PENGEMBANGAN KARIR DI JURUSAN PERBANKAN SYARIAH - Ridwan, Muhammad; Budimansyah, Muhammad (Publikasi Pengabdian Masyarakat, 2023)
This community service aims to socialize the introduction of opportunities and career development in the sharia banking department to students in class XI and XI of State Preparatory Madrasah Aliyah 4 Medan. As the financial industry develops, more and more students are interested in pursuing sharia banking education. Islamic banking is a banking system that operates based on Islamic economic principles. These principles include financial aspects that are in accordance with Islamic sharia law, known as "fiqh muamalah" or economic law in Islam. In contrast to conventional banking which uses interest as its main instrument, sharia banking uses financial mechanisms that are in accordance with Islamic principles, such as sharing profits and risks between the bank and customers using the principle of profit sharing. By delivering material using lecture and discussion methods, we see the importance of socialization regarding the introduction of opportunities and career development in the sharia banking department. The results of this service show that students understand sharia banking and have a great desire to continue their studies in the sharia banking study program.